Overcoming Influenza Vaccination Barriers Through Community Outreach by a Student-Led Mobile Health Clinic - Karakoleva, Ema; Spanos, Katherine; Short, Hannah; Guare, Emma; Lehman, Erik; Mendez Miller, Megan (Journal of Student-Run Clinics, 2024)
Background: Nearly half of United States adults were unvaccinated for influenza in 2022. Suboptimal vaccination rates remain a public health challenge affecting individual and community health. Influenza vaccination hesitancy (IVH) and limited access are especially prevalent among underserved communities. A promising way to combat IVH is through student-led community interventions. The organization Student-Run and Collaborative Outreach Program for Health Equity (SCOPE) at the Penn State College of Medicine (PSCOM) collaborated with community leaders to provide free influenza vaccinations in Central Pennsylvania (PA). We aim to analyze the impact of a student-led clinic on vaccination access and characterize vaccination-related community perceptions and behaviors. Methods: This was a retrospective study. Two health fairs, “Family Wealth Through Health” (FWTH) and HANNA Pantry (HP), in rural PA and urban PA, respectively, were held at the beginning of the flu season (September-October 2022). Surveys assessing vaccine recipient demographics, vaccination status in the previous year, and motivation/intent to vaccinate, were administered. Results were analyzed using chi-square and t-tests. Results: Of 51 respondents, 18 (35.3%) were from FWTH and 33 (64.7%) from HP. Race differed significantly (p<0.001) between sites but age (p=0.203) and sex (p=0.754) did not. One-fifth were unvaccinated the prior year, with reasons being “forgetting,” “health,” “cost,” and “time.” Six participants received vaccinations despite not planning to. Over half reported “doctor’s office” as preferred location for vaccination, others being “pharmacy”, “community health clinic”, “work”, and “store.” Over 20% received earlier-than-planned vaccination at our clinic. Finally, coronavirus disease 2019 (COVID-19) impacted 13.3% of respondents’ willingness to get vaccinated, significantly correlated with prior vaccination status (p=0.011) but not vaccination plans in the current season (p=0.628). Conclusions: Direct influenza vaccination delivery by medical students in rural and urban Central PA improved vaccination uptake, access, and timeliness. Qualitative analysis revealed sociodemographic factors affecting IVH warranting consideration by student-led clinics.